Circuit Stickers: Peel-and-Stick Construction of Interactive Electronic Prototypes - Hodges, Steve; Villar, Nicolas; Chen, Nicholas; Chugh, Tushar; Qi, Jie; Nowacka, Diana; Kawahara, Yoshihiro (Proceedings of CHI 2014, 2014)
We present a novel approach to the construction of elec-tronic prototypes which can support a variety of interactive devices. Our technique, which we call circuit stickers, in-volves adhering physical interface elements such as LEDs, sounders, buttons and sensors onto a cheap and easy-to-make substrate which provides electrical connectivity. This assembly may include control electronics and a battery for standalone operation, or it can be interfaced to a microcon-troller or PC. In this paper we illustrate different points in the design space and demonstrate the technical feasibility of our approach. We have found circuit stickers to be versatile and low-cost, supporting quick and easy construction of physically flexible interactive prototypes. Building extra copies of a device is straightforward. We believe this technology has potential for design exploration, research prototyping, education and for hobbyist projects.